Power generation from slaughterhouse waste materials. An emergy accounting assessment. (20th June 2019) - Santagata, Remo; Viglia, Silvio; Fiorentino, Gabriella; Liu, Gengyuan; Ripa, Maddalena
Abstract: The linear path "extraction-production-consumption-waste", imposed by humans to natural ecosystems, where all material flows are instead circular, has become unsustainable. Understanding the potential value of some of these "by-products", in order to exploit them effectively in a biorefinery perspective, may help overcoming resource shortages and decrease environmental impacts. This study investigates energy and resource restoration from animal by-products. The slaughterhouse waste undergoes a rendering process to separate residual meal and fat. The latter is combusted in a co-generation plant to produce electricity and heat. The process is carefully assessed using Emergy Accounting approach with the aim of evaluating benefits and environmental load of the process considering the advantages achieved compared with the demand for ecosystem services and natural capital depletion. Moreover, the case aims at exploring three different methodological assumptions referring to the upstream burdens carried by the waste management system, proposing a modified exergy-based allocation rule. The electricity generated shows performances in terms of Unit Emergy Values ranging between 2.7E+05 sej/J, 2.2E+06 sej/J and 3.1E+07 sej/J among the different cases investigated, comparable to power from fossil fuels and renewables sources, and it provides an environmentally sound alternative to conventional waste disposal. Highlights: Linear "take-make-dispose" patterns in food production are environmentally unsustainable. Circular strategies improve the environmental and economic performances of food chain. Electricity generation out of slaughterhouse waste is suggested as a circular alternative to landfilling. A modified emergy approach is applied for the evaluation of resource and waste intensive processes. The emergy approach allows a comprehensive sustainability understanding to integrate monetary and LCA evaluations.